VALUE OF LEADERSHIP IN SOEKARNO FILM (Study of Pentad Analysis on The Movie “Soekarno” by Hanung Bramantyo) - Aldo Robbyansyah; Panji Dwi Ashrianto; Senja Yustitia (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2018)
In Indonesia, the issue of corruption is still a serious problem. According to KPK, there were 670 corruption cases from 2004 to June 2017. The issue of corruption is often associated with the lack of an exemplary figure in Indonesia who is clean and has integrity. If it is connected with the world of film that often portrays the phenomenon of society, the scarcity of integrity figures makes many films that still present characters from the past such as in the film Sukarno. This research was conducted to find out how the representation of leadership values in Sukarno's film used the advanced analysis method and the theory of dramaticism. This study concluded that the values of leadership in Soekarno's film were shown in five important elements consisting of scenes, agent, act, agency, and purpose. Soekarno's leadership emerged in certain circumstances when Soekarno faced the Dutch the character of leadership changed aggressively, bravely, without compromise. When facing Japan, Soekarno using political and diplomatic strategies. Also included with the people, Soekarno is more featuring a harmonious, democratic and family concept.